(untitled) (Journal of Engineering, 2024)
The lightweight concrete is manufactured from aggregates (expanded perlite) with a density of 145 kg/m3 and an absorption of 1.65%. This study has two aspects: a theoretical aspect that includes previous research on this concrete and a practical aspect that provides for conducting two groups of mixtures and preparing them according to ACI 211.2-98 design method. The first group includes cement, perlite, and water, and the second group consists of the addition of superplasticizer and silica fume, Each group included five series with three variables for each series. In the first series, the cement content was changed with a content of (275,300,350) kg/m3 with a volumetric mixing ratio (1:4), while in the second series, the aggregate content was changed only with a cement content of (275) kg/m3 with mixing ratios (1:4.1:5, 1:6) with a ratio of water to cement (0.4), and in the third series (superplasticizer) type (F) is added in different proportions, in the fourth series silica fume was added in three proportions (5%, 10%, 15% ) By replacing the weight of cement and the fifth series, the optimum contents were determined, which have acceptable workability, low density, and compressive strength commensurate with the density. Tests (flowability, dry density, and compressive strength) were carried out. It was observed that the workability, dry density, and compressive strength decreased with increasing perlite content but improved with the addition of superplasticizer and silica fume. The percentage of increase in density was (9% and 32%) at the optimum value of silica fume in 28.7 days, respectively. As for the compressive strength, the percentage of increase was (30% and 36%) in 7 and 28 days, respectively.